The Role of Emotional Intelligence in Shaping Students' Social Behavior - Tika Tika; Kabri Kabri; Ponijan Ponijan (CV. Rayyan Dwi Bharata, 2024)
This research investigates the role of emotional intelligence in shaping students' social behavior by adopting a systematic literature analysis approach. Emotional intelligence, as an important dimension in individual development, has become a focus of attention in the educational context. Through a review of current research, this research aims to construct a comprehensive understanding of how emotional intelligence influences social interactions, conflict resolution, and the development of students' interpersonal skills. The main findings indicate a positive relationship between the level of emotional intelligence and students' social behavior, with significant implications for the development of holistic educational approaches. The conclusions of this study reinforce the urgency to include emotional intelligence in the curriculum, while emphasizing the need for intervention programs that can improve students' social skills. These findings also stimulate thought regarding the need to understand the role of emotional intelligence in cultural and environmental contexts. Therefore, further research that considers contextual factors is needed to gain deeper insights.